Phon kāndamn̄œn ngān 3 pī kh̨ōng ratthabān Nāyok Ratthamontrī Chūan Līkphai : Ph̨ō. Y̨ō. 2540 - Ph̨ō. Y̨ō. 2543 (Samnak Kh̨ōsok, Samnak Lēkhāthikān Nāyok Ratthamontrī, 2000)
The works of the Chūan Līkphai government from 1997 to 2000.